2017
DOI: 10.1371/journal.pone.0183102
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic T cell expansion correlates with severity of peripheral vascular damage in systemic sclerosis

Abstract: The mechanisms underlying endothelial cell injury and defective vascular repair in systemic sclerosis (SSc) remain unclear. Since the recently discovered angiogenic T cells (Tang) may have an important role in the repair of damaged endothelium, this study aimed to analyze the Tang population in relation to disease-related peripheral vascular features in SSc patients. Tang (CD3+CD31+CXCR4+) were quantified by flow cytometry in peripheral blood samples from 39 SSc patients and 18 healthy controls (HC). Circulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 31 publications
2
36
0
Order By: Relevance
“…The IMMENSE study provides novel insights into the evaluation of CV subclinical alterations in SLE by unveiling some potential aspects of the complex interplay between T ang , EPCs, and endothelial cells. The focus of the study was on circulating T ang cells, which were recently demonstrated to be a potentially useful biomarker reflecting vascular alterations in CV and autoimmune diseases (10,11,32,33). In our highly selected young SLE patients without previous CV events and a low rate of traditional CV risk-factors, we found a mild decrease of T ang cells in patients in comparison with HCs, confirming our previous observation (34).…”
Section: Discussionsupporting
confidence: 86%
“…The IMMENSE study provides novel insights into the evaluation of CV subclinical alterations in SLE by unveiling some potential aspects of the complex interplay between T ang , EPCs, and endothelial cells. The focus of the study was on circulating T ang cells, which were recently demonstrated to be a potentially useful biomarker reflecting vascular alterations in CV and autoimmune diseases (10,11,32,33). In our highly selected young SLE patients without previous CV events and a low rate of traditional CV risk-factors, we found a mild decrease of T ang cells in patients in comparison with HCs, confirming our previous observation (34).…”
Section: Discussionsupporting
confidence: 86%
“…In addition, a more recent study has confirmed that Th2 and Th17 cells are found in higher frequencies in SSc patients, and this was found to positively correlate with IL-35 levels, although a causal link has not been established [58]. Further evidence of disruption to T cell homeostasis comes from a recent study showing that SSc patients displaying severe peripheral vascular complications have an expansion of the recently discovered angiogenic T cells [59]. This expansion in angiogenic T cells may also demonstrate a link between immune cell activation and vasculopathy in SSc.…”
Section: T Cellsmentioning
confidence: 99%
“…In SSc, Tang cell counts have been reported to be selectively increased in the PB of SSc patients with severe vascular complications like digital ulcers and there was an inverse correlation between circulating Tang and EPCs (defined as CD34 + CD133 + VEGFR2 + ). Furthermore, the presence of circulating Tang cells positively correlated with the levels of pro-angiogenic factors, namely VEGF and MMP-9 ( 56 ). Such Tang cell expansion has, therefore, been suggested as a possible ineffective attempt to compensate the decrease in EPC number ( 56 ).…”
Section: Epcs In Sscmentioning
confidence: 99%
“…Furthermore, the presence of circulating Tang cells positively correlated with the levels of pro-angiogenic factors, namely VEGF and MMP-9 ( 56 ). Such Tang cell expansion has, therefore, been suggested as a possible ineffective attempt to compensate the decrease in EPC number ( 56 ).…”
Section: Epcs In Sscmentioning
confidence: 99%